A situação da violência doméstica durante a covid-19: estudo quantitativo na cidade de Bauru-SP - Guaraldo, Tamara de Souza Brandão [UNESP]; Santos, Celia Retz Godoy dos [UNESP] (Instituto de Comunicacao e Informacao Cientifica e Tecnologica em Saude, 2023)
This article is part of a report based on a survey carried out by Unesp in partnership with the Municipal Council of Policies for Women, Bauru-SP on domestic violence, from June to August 2020. The non-probabilistic research, of descriptive nature, used the online questionnaire to collect data. The survey was conducted to find out woman opinions, in order to offer parameters to support communication and publicity actions for the service provided by a network for combating violence against women in that city. Its results generated fundamental information for dissemination of rights, laws, protective measures, campaigns and prevention, among other ways of giving visibility to the service provided by that network. They made possible to plan communication strategies based on the community opinion, appropriate to demands and peculiar needs for each region approached by the survey, which enabled to monitor and evaluate that network.